Study on designation of cyber information assurance education in USA - Ning ZHANG; Hui LI (网络与信息安全学报)
National centers of academic excellence-cyber defense and cyber operation programs sponsored by NSA and DHS in USA were introduced and analyzed. The basic criteria and procedure of national centers of academic excellence-cyber defense with three programs, 2 years/4 years education and research center were introduced, as well as the national centers of academic excellence-cyber operation with the basic criteria. The Curriculum i.e. knowledge units were analyzed in detail. The development and current situation of the designations were investi-gated. Hopefully the study would be helpful to improve the accretion of the discipline of cyber security in our country.